Dampak Perubahan Paradigma Baru Matematika Terhadap Kurikulum dan Pembelajaran Matematika di Indonesia - Wahyudi Wahyudi; Hardi Suyitno; St. Budi Waluya (INOPENDAS: Jurnal Ilmiah Kependidikan, 2018)
Mathematics provides many benefits to human life and continues to grow. The development of mathematics begins with a paradigm shift of mathematics from experts and society. The paradigm of a person about mathematics will affect the way he learns and knows more about mathematics. This paradigm shift affects the changes in the implementation of the education system that impacts the curriculum, learning, and evaluation of mathematics learning. In addition, this paradigm shift also raises some problems in learning mathematics. This paper will provide an overview of how the journey of change of mathematical paradigm from time to time and give an idea of how the mathematics curriculum developed and how the pattern of learning and evaluation of mathematical learning done in the current era. In addition, this paper also provides an overview of the problems of mathematics education in Indonesia and its comparison from several countries namely Finland, Canada and Japan.